2021
DOI: 10.1002/adfm.202110771
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Mechanically Induced On–Off Photoluminescence in Hybrid Metal Halides

Abstract: Stimulus-responsive photoluminescent materials have attracted extensive research attention in recent years owing to their potential application in information storage and switch devices. It is important to further explore such bistable materials as well as the underlying transformation mechanisms. Herein, the syntheses and mechanically tunable "on-off" photoluminescence (PL) of two organic-inorganic hybrid metal halides, (Bmpip) 9 Pb 3 Zn 2 Br 19 and (Bmpip) 9 Pb 3 Cd 2 Br 19 (Bmpip + = 1-butyl-1-methyl-piperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Temperature-dependent PL characterization of 1−4 was performed under ∼417 nm excitation (Figures 3 and S5). 43 Compounds 1−3 exhibited a single LE emission at 77 K, and the HE peak in 4 also weakened significantly at 77 K. This phenomenon proved that the main emission mechanism at low temperature was the d−d transition of Mn 2+ . As the temperature increased, the electrons in [MnCl 6 ] 4− could gain enough energy to transfer back to the excitation energy level of the organic cations, so the intensity of the HE peaks was enhanced.…”
Section: ■ Introductionmentioning
confidence: 72%
“…Temperature-dependent PL characterization of 1−4 was performed under ∼417 nm excitation (Figures 3 and S5). 43 Compounds 1−3 exhibited a single LE emission at 77 K, and the HE peak in 4 also weakened significantly at 77 K. This phenomenon proved that the main emission mechanism at low temperature was the d−d transition of Mn 2+ . As the temperature increased, the electrons in [MnCl 6 ] 4− could gain enough energy to transfer back to the excitation energy level of the organic cations, so the intensity of the HE peaks was enhanced.…”
Section: ■ Introductionmentioning
confidence: 72%
“…Stimuli-responsive luminescent materials, with a specific response to external stimuli such as light, 1 pressure, 2 solvent molecules, 3 and heat, 4,5 have attracted extensive research interest and have shown wide application potentials in information storage, 6–8 chemical sensing, 9–11 and anti-counterfeiting. 12–15 In particular, thermosensitive materials are praised for their simple heating device requirement, highlighting their applications in thermal imaging, and thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 0-D IOMHs may own soft lattice and strong electron–phonon coupling, thus leading to interesting photoluminescent properties, including broad emission and large Stokes shift [ 10 ]. As a result, the applications of photoluminescent 0-D IOMHs have flourished in light-emitting diode [ 11 , 12 , 13 , 14 , 15 ], X-ray scintillator [ 16 , 17 , 18 ], remote thermography [ 19 , 20 ], optical waveguide [ 21 ], anti-counterfeiting [ 22 , 23 , 24 , 25 , 26 ], as well as sensor [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%